2018
DOI: 10.1101/310037
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Corals sustain growth but not skeletal density across the Florida Keys Reef Tract despite ongoing warming

Abstract: 23Through the continuous growth of their carbonate skeletons, corals record invaluable information 24 about past environmental conditions and their effect on colony fitness. Here, we characterize 25 century-scale growth records of inner and outer reef corals across ~200 km of the Florida Keys 26Reef Tract (FKRT) using skeletal cores extracted from two ubiquitous reef-building species, 27Siderastrea siderea and Pseudodiploria strigosa. We find that corals across the FKRT have 28 sustained extension and calcific… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 70 publications
1
5
0
Order By: Relevance
“…The entire length of the core was analyzed in this manner, or until it was no longer possible to resolve annual growth bands due to the effects of bioerosion and/or loss of seasonal density banding. Additional details on this methodology, including example images of coral CT scans, can be found in Figure S1 and in Rippe et al (). Data for the individual cores analyzed in this experiment, including length of each growth record, are provided in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The entire length of the core was analyzed in this manner, or until it was no longer possible to resolve annual growth bands due to the effects of bioerosion and/or loss of seasonal density banding. Additional details on this methodology, including example images of coral CT scans, can be found in Figure S1 and in Rippe et al (). Data for the individual cores analyzed in this experiment, including length of each growth record, are provided in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…To validate the use of linear extension as a proxy of coral calcification in this study, skeletal density and calcification rate were also calculated for all cores collected and CT scanned in 2015 ( n = 68 cores). Coral density standards of known mass and volume were obtained from coral cores with the same diameter as those used in the study and scanned alongside the corals to construct a standard curve for each scanning session that correlated Hounsfield unit values (CT scan output) to density (g/cm 3 ; DeCarlo et al, ; Rippe et al, ). In this study, extension rate was well correlated with calcification rate ( p < .001, R 2 = 0.919 for S. siderea and p < .001, R 2 = 0.598 for P. strigosa ), while density is not ( p < .001, R 2 = 0.052 for S. siderea and p < .001, R 2 = 0.002 for P. strigosa ; Figure S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although such studies have been conducted by gamma densitometry (Lough & Barnes, 1990) for decades (as reviewed by Barnes & Lough, 1996; Lough, 2008, 2010; Lough & Cantin, 2014; Lough & Cooper, 2011), these new approaches permit comparably rapid assessment of multiple tracks along a slab and within 3D coral cores (Figure 2b). Application of these techniques have: (1) determined the effect of warming and ocean acidification (OA) on coral growth (e.g., Cantin et al, 2010; Cooper et al, 2012; Helmle et al, 2011; Mollica et al, 2018; Rippe et al, 2018) and bioerosion (from boring bivalve, worms, and sponges, DeCarlo, Cohen, et al, 2015); (2) identified historical bleaching‐related growth anomalies (Barkley et al, 2018; Barkley & Cohen, 2016; Cantin & Lough, 2014; Carilli et al, 2010, 2012; DeCarlo et al, 2019); (3) estimated bleaching susceptibility (e.g., percentage of the coral community bleached, Barkley & Cohen, 2016; Mollica et al, 2018); and (4) assessed reef recovery following disturbance (Cantin & Lough, 2014).…”
Section: Insights Into Tropical‐subtropical Climate Variability and C...mentioning
confidence: 99%